Factors associated with participation in resistance training: a systematic review. Issue 20 (12th April 2017) - Rhodes, Ryan E; Lubans, David R; Karunamuni, Nandini; Kennedy, Sarah; Plotnikoff, Ronald
Abstract : Objective: Regular participation in resistance training (RT) is critical to health and recommended in most international physical activity guidelines. Few people, however, participate in RT. The purpose of this review was to assess the demographic, behavioural, intrapersonal, interpersonal and environmental factors associated with participating in RT. Data sources: Eligible studies were from English peer-reviewed published articles that examined correlates or determinants of RT in adult samples. Searches were performed from August 2015 to April 2016 in six databases. Results: We identified 51 independent data sets, from nine countries, primarily of moderate to high quality, and 23 factors related to participating in RT. Education, perceived health status, quality of life, affective judgements, self-efficacy, intention, self-regulation behaviours, subjective norm and programme leadership were associated with RT. Conclusion: Low education levels and poor health status were associated with low participation rates in RT. Intrapersonal factors including affective judgements, self-efficacy, and self-regulation behaviours, and interpersonal factors including subjective norms and programme leadership may be important for promoting RT behaviours.